Reflection of Deobandi Religious Education for Multicultural Education in Indonesia - Tanasyah, Yusak; Betaubun, Jiefard Stanley (MODERATE: Journal of Religious, Education, and Social, 2024)
Since the last USA troop is withdrawal from Afghanistan July 2021, there is new era of people Afghanistan. People of Afghanistan now under Taliban army as their start to take over all over the city in Afghanistan. At the turn of the twenty-first century, grant and arrangement talk about on Islam and Muslim social orders has come to center basically on Islam’s capacity to form youthful Muslim’s float towards anti-modernity developments. Numerous quality Islamic militancy, as well as the common socio-economic and political stagnation experienced in a few Muslim social orders, to Islamic religious or legitimate directs. However Islamic insightful convention is exceedingly pluralistic, and today’s driving Islamic specialist structures are creating competing conceptual and methodological approaches which shift incredibly in their capacity to lock in with societal alter. Established as a grassroots movement for religious education in the wake of the 1857 Sepoy Rebellion in India, the Deoband ‘ulama continue to flourish and to carry the mantle of “custodians of change” with increasingly activist vigor. What are the repercussions of this growth, and how does this contribute to an understanding of the complex interrelation of Sufism, pluralism, and democracy? Could we reflecting the Deobandi religious education to perform new era of Taliban in Afghanistan who tolerate economic development, multicultural, freedom religion, and women right in the context of multicultural education in Indonesia? This research analyzes concerns related to religious extremism in Afghanistan and prospect of possible actions for countering the threat. Education performed a critical role in the nation’s building as it fills the gap between information and knowledge. It takes shortfall of information among the different divisions of a nation state.   Contrbution: The article "Reflection of Deobandi Religious Education for Multicultural Education in Indonesia" examines the Deobandi movement's impact on religious education and its relevance to Indonesia's multicultural society. It explores how Deobandi principles, emphasizing religious conservatism and anti-Western sentiment, can be reframed to contribute positively to Indonesia's multicultural education system. The research advocates for integrating Deobandi religious teachings into a broader educational framework that promotes understanding and respect for religious diversity, aligning with Indonesia's diverse cultural and religious landscape.